2018
DOI: 10.3390/soc8020025
|View full text |Cite
|
Sign up to set email alerts
|

Supported Decision-Making from Theory to Practice: Implementing the Right to Enjoy Legal Capacity

Abstract: The right to equal recognition before the law, protected by Article 12 of the United Nations (UN) Convention on the Rights of Persons with Disabilities (CRPD), mandates the use of supported decision-making practices to enable disabled people, particularly those with intellectual and/or psychosocial disabilities, to enjoy their legal capacity. Finding ways to translate this theoretical mandate into practice poses a number of particularly challenging socio-legal issues, which this research seeks to address. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
2
27
0
2
Order By: Relevance
“…Many participants identified having a variety of choices in their life and it was noted by some that the opportunities to make choices had improved over the years. Generally, the opportunity to make decisions was considered to be a positive experience which resonates with the findings from Harding & Taşcıoğlu’s () study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Many participants identified having a variety of choices in their life and it was noted by some that the opportunities to make choices had improved over the years. Generally, the opportunity to make decisions was considered to be a positive experience which resonates with the findings from Harding & Taşcıoğlu’s () study.…”
Section: Discussionsupporting
confidence: 65%
“…Other studies have also discussed the relationship between the individual and the supporter, particularly focusing on the individual's feeling of powerlessness if there was not a good working relationship between them (McDaid & Delaney, ; Jamieson, Theodore, & Raczka, ; People First (Scotland), ). Harding & Taşcıoğlu’s () qualitative study with people with intellectual disabilities in England reported a range of positive practice, especially for everyday decision‐making, although more difficult decisions were reported to be less well‐supported.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of mental capacity has become a key component of daily clinical practice [4,5]. Mental health legislation and medical ethics increasingly require physicians to empower patients to make decisions, and to respect the patient's wishes with regard to accepting or refusing therapy [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…A person’s autonomy, according to person-centered care, relies more on his or her relational and social context than what is proposed in individualist- and cognitive-based approaches to autonomy 24. Furthermore, next of kin, through so-called supported decision-making,25,26 may assist in increasing the autonomy of a person with cognitive impairment. Decision-making processes in person-centered care are characterized by a dynamic dialog between the patient, their next of kin, and health care personnel 27…”
Section: Introductionmentioning
confidence: 99%